Analysis of Hyperemesis Gravidarum that Occurs in Pregnant Women at the Balaraja Health Center - Rosmiati Rosmiati; Lilik Susilowati (Akademi Keperawatan RSPAD Gatot Soebroto, 2022)
The purpose of this study was to analyze the incidence of hyperemesis gravidarum in pregnant women. This research is analytic in nature using a cross sectional design. This research was conducted at the Balaraja Health Center in 2021. The population in this study were all pregnant women who were diagnosed with hyperemesis gravidarum. The population in this study were 22 pregnant women with hyperemesis gravidarum. The analytical method in this study, namely, univariate analysis and statistical methods using the frequency distribution to see an overview of the characteristics of pregnant women who experience hyperemesis gravidarum including age, education, gravida and treatment. The results of this study are the variable age of pregnant women 20-35 years with hyperemesis gravidarum of 86.4% while age> 35 years of 13.6%. In variable gravida 2-4 (multigravida) with hyperemesis gravidarum it is 63.7%, in gravida 1 (primigarvida) it is 31.8% and in multi grande gravida > 4 it is 4.5%. At the elementary level education variable with hyperemesis gravidarum was 50%, junior high school level was 40.9%, high school level was 9.1%. In the variable handling of hyperemesis gravidarum, 95.4% were treated and 4.6% referred. The conclusion obtained is that hyperemesis gravidarum is a problem or diagnosis that often occurs, especially in the first quarter of pregnancy and can continue throughout pregnancy marked by excessive nausea and vomiting until dehydration and urine acetoses and impaired consciousness. Treatment of hyperemesis gravidarum is to determine the level of hyperemesis gravidarum based on the clinical symptoms that arise, namely mild, moderate and severe. And pay attention to the amount of electrolyte fluid that will be entered through the infusion.